Konsep dan Urgensi Konstitusi dalam Kehidupan Berbangsa dan Bernegara - Dinda Meirani; Isnadiatul Husna; Aulia Indira (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Indonesia is known as a state of law, as stated in its constitution. This shows that state administration in Indonesia is not solely based on power. A state cannot be formed without a constitution. The constitution is an essential element in the constitutional structure that must exist and cannot be separated. The function of the constitution is to regulate government power so as not to exceed its limits, in order to protect the rights of citizens. The method used in this research is a library research method sourced from journals. The results and conclusions of this study are the reasons for the need for a constitution in the life of the nation and state, historical, sociological, and political sources of the constitution in the life of the nation and state in Indonesia, arguments about the dynamics and challenges of the constitution in the life of the nation and state in Indonesia, the essence and urgency of the constitution in the life of the nation and state, conclusions about the constitution, civic practice.